The acceptance of consumers on anti-radiation products for smartphone towards purchase intention / Nurul Nazahatul Naimah Mohd Rais - Mohd Rais, Nurul Nazahatul Naimah (Faculty of Business and Management, 2017)
The aim of this study is to identify the acceptance of consumers towards anti-radiation products for smartphone towards purchase intention. This research explores the relationship between perceived values, perceived risk, product knowledge, and products involvement on purchased intention towards anti-radiation products for smartphone. Data collected analyzed by using Statistical Package for the Social Science (SPSS) for windows. This research was conducted at Misi Setia Oil & Gas, Semenyih, which will specifically focus on the employees only. In this research, 70 sets questionnaire had been distributed. All the respondents will be responding from questionnaire that will provide to get the result on the acceptance of consumers towards anti-radiation products for smartphone towards purchase intention. All the four major of independent variable will be explained in the literature review and research framework.